Impact of Phenolic Removal on the Molecular and Functional Properties of Sunflower Seed Cake Proteins - Vartiya, Pooja; Kashyap, Piyush (Asian Journal of Chemistry, 2026)
Sunflower seed cake (SSC), the major by-product of oil extraction, is considered an under utilised protein resource due to its abundance. The nutritional quality and functionality of protein fractions in SSC are negatively affected by phenolic compounds. This study compared the functional and nutritional properties of phenolised and dephenolised protein fractions. Dephenolisation using ethanol extraction reduced the total phenolic content significantly and improved the purity and yield of proteins. Significant improvements were recorded in functional traits: water-holding capacity, oil-holding capacity, emulsifying activity and foaming capacity, after the removal of phenolics. Nutritionally, dephenolised fractions had higher purities and yields due to exposure of active sites that were being held internally within phenolic complexes. Of all fractions, globulin and albumin elicited better functional and nutritional performance upon dephenolisation. Overall, these findings confirm dephenolisation as an appropriate pretreatment to enhance protein functionality in SSC, supporting its application in sustainable food formulation and protein-enriched products.